Pengaruh Kompetensi Profesional, Kompensasi, dan Disiplin terhadap Kinerja Guru - Siti Suaedah (Universitas Indraprasta PGRI Jakarta, 2020)
The purpose of this study is to determine whether there is an effect of pedagogic competence, compensation, and discipline on the performance of junior high school teachers in South Jakarta. The method used in this study was quantitative using the survey method with multiple linear regression. This research was conducted from September 2018 to February 2019. This research was conducted by distributing questionnaires to 83 respondents who were junior high school teachers in South Jakarta. Based on the research results, it was obtained that a correlation value of 0.902, it indicated a very strong correlation coefficient value, the value of the termination coefficient was 81.4%. The value of the regression equation was Y = 13.41 + 0.723X1 + 0.048X2 + 0.153X3, it indicated the direction of the regression equation was positive. Hypothesis testing results obtained F value counting 116.55 where it was > 0.05, this indicated that there was a joint influence of the variables of Professional Competence, Compensation, and Discipline on the Performance of Junior High School Teachers in South Jakarta.